The effect of rehabilitation procedures used during training on the state of the autonomic nervous system in professional basketball players - Andreev, D. S.; Konovalov, I. E.; Parfenova, L. A.; Andreev, V. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study is aimed at analyzing the dynamics of the vegetative state in professional basketball players, depending on the use of various recovery methods in the training process.